PERTANGGUNGJAWABAN PIDANA KORUPSI TERHADAP DANA HIBAH APBD TERKAIT PENYELENGGARAAN SOSIALISASI PEMILIHAN UMUM DI KPU KABUPATEN PAKPAK BHARAT - Bahagia Halawa; Davin Suryamana Barus; Tomi Mangaratua Butar-Butar; Sonya Airini Batubara (Jurnal Darma Agung, 2019)
Corruption is a deviant behavior from normal duties of the government agencies’ role because of personal interest (family, group, friends or colleague) to fulfill status and prestige, or breaking the rules by doing or looking for influence for the sake of personal gain.This research used normative juridical method or used invitation law approach. In other words, it can be said as an approach to a problem researched focused and as a theme of a research toward the responsibility of criminal corruption of Regional Expenditure Budget grant in organizing election socialization in General Election Commissions (KPU) of Pakpak Barat Regency and to know the legal consideration by the judge in giving the decision of corruption in Regional Expenditure Budget grant in Pakpak Barat Regency. The finding of this research is how law arranged toward criminal corruption, that is arranged in constitution No. 31 of 1999 as changed by Constitution No. 31 of 2001 about The Eradiction of Criminal Acts of Corruption, Regional Expenditure Budget grant in election socialization regulated by the Minister of Home Affairs Regulation No. 14 of 2016 about the guidelines for grants and social assistance sourcing of Regional Expenditure Budget. The responsibility of corruption of Regional Expenditure Budget grant in organizing election socialization of General Election Commissions in Pakpak Barat Regency is already accordance with a sense of justice, received by both defendants, in which except of them some of General Election Commissions’ commissioners were made as defendants also but from sentence side it is not appropriate with purpose of eradicting corruption in Indonesia. The judge’s consideration ingiving a corruption decision in the implementation of election socialization at the District Election Commission of Pakpak Bharat was appropriate where the actions of the two perpetrators were illegal acts that participated in the misuse of state finances.